Pengelolaan Sampah di Kota Pekanbaru - Ernawaty Ernawaty; Zulkarnain Zulkarnain; Yusni Ikhwan Siregar; Bahruddin Bahruddin (Universitas Riau, 2019)
Waste is a wasted or intentionally disposed material derived from the results of human and natural activities that do not have economic value. Pekanbaru city is one of the city that does not escape from garbage problem. The waste management of Pekanbaru City includes the final collection, collection, transportation, processing and disposal. Current waste management has not solved the problem optimally. The concept of waste management conducted by urban community Pekanbaru at this time mostly only tn the conte.xt of transporting waste from waste sources to landfills (FPA) which then will have an impact on the environment and health around the TPS are supported also with the behavior of people who are still mixing between dry waste and wet garbage. Type of research is done by qualitative approach with descriptive method Based on field facts with data collection techniques include observation, interviews, docwnentation studies related to research objectives. This research uses Hartono theory which mentions 5 stages of the applied process, namely prevent, reuse, recycle, capture energy and waste. The informant of this research is the administrative staff of Garbage Management Sector Pekanbaru City, Section Head of Solid Waste Management of Domestic Riau Province, and Chairman of Swadaya Masyarakat